Formulation Development, Characterization, and Evaluation of Controlled Nasal Drug Delivery Systems for Cefuroxime Axetil (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: This current study objective is to develop cefuroxime axetil (CA) nasal mucoadhesive microspheres for an alternative utilization of dosage form for respiratory tract infections Materials and Methods: CA microspheres were prepared by modified emulsion-lyophilization method in which chitosan and beta-cyclodextrin were used as a release retardant polymer. The model is optimization by 24 factorial designs and validated using ANOVA. CA microspheres evaluated for entrapment efficiency, ex vivo mucoadhesion and % drug release. The optimized formulations were performed for its Fourier transform infrared (FT-IR) analysis, particle size and polydispersity index (PDI) and zeta potential, thermal analysis DSC and XRD, and surface morphology by scanning electron microscopy followed by in vitro and ex vivo release kinetic studies. Key Findings: Results of these evaluations showed that entrapment efficiency was found to be 69.21–80.45%, particle size in the range of 12.55–17.22 μm, mucoadhesion in the range of 72.51–79.68%, and drug release in the range of 72.21–83.65%. FT-IR studies ensured that no drug-polymer interaction in the formulated microspheres. PDI and zeta potential were measured and the mean particle size and distribution of microspheres were in the range and the surface topography revealed a spherical surface for all the formulations and a round cavity enclosed by an outer shell composed of the drug and polymer. DSC and XRD were found to be in fairly acceptable and in vitro and ex vivo release profile of microspheres formulation was found to be 80.25 and 76.28% at the end of 6 h. Stability studies for 6 months revealed that the optimized formulation was stable, no changes in physical appearance. Conclusion: Finally, it was concluded that the nasal microspheres of CA may have potential enough for effective drug delivery